Characterization of In Vitro Expanded Bone Marrow-Derived Mesenchymal Stem Cells Isolated from Experimental Autoimmune Encephalomyelitis Mice - Dimitra Zacharaki; Roza Lagoudaki; Olga Touloumi; Konstantia Kotta; Antiopi Voultsiadou; Kyriaki-Nepheli Poulatsidou; Athanasios Lourbopoulos; Georgios Hadjigeorgiou; Efthimios Dardiotis; Dimitris Karacostas; Nikolaos Grigoriadis (Journal of Molecular Neuroscience, 2013)

Flexible modeling for stock-recruitment relationships using Bayesian nonparametric mixtures - Kassandra Fronczyk; Athanasios Kottas; Stephan Munch (Environmental and Ecological Statistics, 2012)

Bayesian analysis of size‐dependent overwinter mortality from size‐frequency distributions - Stephanie M. Carlson; Athanasios Kottas; Marc Mangel (Ecology, 2010)
Understanding the relationship between body size and mortality is an important problem in ecology. We introduce a novel Bayesian method that can be used to quantify this relationship when the only data available are size‐frequency distributions of unmarked individuals measured at two successive time periods. The inverse Gaussian distribution provides a parametric form for the statistical model development, and we use Markov chain Monte Carlo methods to evaluate posterior distributions. We illustrate the method using data on threespine stickleback ( Gasterosteus aculeatus ) collected before and after the winter season in an Alaskan lake. Our method allows us to compare the intensity of size‐biased mortality in different years. We discuss generalizations that include more complicated relationships between size and survival as well as time‐series modeling.